Strategic Principal Leadership in Enhancing Teacher Performance: A Case Study of a Remote Plantation-Based Junior High School in Indonesia - Nurlela Nurlela; Achadi Budi Santosa; Emmanuel Etim Uye (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to deeply explore the role of the principal in improving teacher performance by emphasising three main approaches: managerial, supervisory, and motivational. This study employed a qualitative case study approach. Data were collected through in-depth interviews with five teachers with more than ten years of work experience. Data were then verified through classroom observations and school document analysis to ensure the validity of the information. Data analysis was conducted using thematic techniques to identify patterns of the principal's role in daily practice. The results indicate that the principal strategically builds a conducive work environment, provides clear direction through academic supervision, and encourages teacher motivation with rewards and professional development opportunities. Collaboration between the principal and teachers has been shown to increase the effectiveness of the learning process and help schools achieve educational quality targets. This study concludes that effective principal leadership is a determining factor in successful teacher performance in remote areas. The implications of this study emphasise the importance of principal leadership competency development programs and provide input for formulating educational policies in areas with similar characteristics.